Characterisation of Glass Fibre Polypropylene and GFPP based Fibre Metal Laminates at high strain rates - Govender, Reuben Ashley (Blast Impact and Survivability Research Unit, 2017)
Fibre reinforced polymers (FRP) are finding increasing use in structures subjected to high rate loading such as blast or impact. Proper design of such structures requires thorough characterisation of the material behaviour over a range of loading rates from quasi-static to impact. This thesis investigated the quasi-static and impact response of Glass Fibre Polypropylene (GFPP) in compression, bending and delamination. The bending and delamination response of Fibre Metal Laminates (FMLs) based on GFPP and aluminium was also investigated at quasi-static and impact rates. High strain rate (5x10^2 to 10^3 /s) compression tests were conducted on GFPP using a compressive Split Hopkinson Pressure Bar (SHPB) and a Direct Impact Hopkinson Pressure Bar (DIHPB), in the through-thickness and in-plane directions. In both loading directions, the peak stress of GFPP increased linearly with the logarithm of strain rate. For in-plane loading, the failure modes were dominated by localised fibre buckling and kink bands, leading to delamination. The through thickness loading produced macroscopic shear and spreading failure modes. However, both of these failure modes are linked to in-ply fibre failures, due to through thickness compression causing transverse tensile strain. Previous studies of similar materials have not explicitly stated the link between through thickness compression and fibre failure associated with transverse tensile strain. A novel test rig was developed for Three Point bend testing at impact rates. The specimen was supported at the outer points on a rigid impacter and accelerated towards a single output Hopkinson Pressure Bar (HPB), which impacted the specimen at its midspan. Previous impact bend test rigs based on HPBs were limited to testing specimens with deflections to failure up to approximately 1mm, whereas the rig implemented herein measured deflections up to approximately 10 mm. This configuration permits the output HPB to be chosen purely on the magnitude of the expected impact force, which resulted in superior force resolution to configurations used in other studies. The HPB Impact Bend rig was used to test GFPP and aluminium-GFPP FML specimens, at impact velocities ranging from 5 to 12 m/s. The flexural strength of GFPP increased with strain rate, while the flexural response of the FML specimens was relatively insensitive to strain rate. v Several candidate delamination test geometries were investigated at quasi-static displacement rates (1 mm/min), and the Single Leg Bend (SLB) test was identified as suitable for adaptation to higher rate testing. Single Leg Bend delamination tests of both GFPP and FML specimens were performed using the HPB Impact Bend rig, at impact velocities of 6 to 8 m=s. The shape of the force displacement response for the high rate testswas markedly different from the quasi-static tests, for both the GFPP and FML specimens. Finite element (FE) simulation of the quasi-static and impact rate SLB tests on GFPP indicated that the difference was probably due to the interaction of flexural vibrations and stress waves in the specimen and the impacter cross member. The experimental results and FE analysis suggest that the delamination fracture toughness of GFPP decreases slightly as strain rate increases. High rate delamination tests on FML specimens resulted in unstable crack growth.